Building a Green, Resilient, and Inclusive Recovery - Malpass, David (Washington, DC: World Bank, 2021)
World Bank Group President David Malpass acknowledged the importance of the United Kingdom within the World Bank Group. He spoke about the Coronavirus (COVID-19) which descended on the poor like wildfire. He highlighted the Bank's approach to the interlinked crises of green, resilient, inclusive development (GRID). The World Bank is working to help countries build “Country Platforms” to engage with wider groups of development actors as they develop the programs with Bank support. He focused on three of the most pressing challenges of climate, debt, and inequality. There is a need for integrated, long-run strategies that emphasize green, resilient, and inclusive development. He concluded we can generate a recovery that ensures a broad and lasting rise in prosperity especially for the poorest and most marginalized.